IMPLEMENTASI LESSON STUDY PADA MATA KULIAH KAPITA SELEKTA MATEMATIKA SMP UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Indah Puspita Sari; Adi Nurjaman (Jurnal Ilmiah P2M STKIP Siliwangi, 2016)
This research aims to improve the learning outcomes of students in the subject of Capita Selecta Mathematics in middle school through the implementation of Lesson Study. This research is a class action research in which the subject are the students of class A2 2014. The students are from regular class that consists of 41 students. The research was conducted in 4 cycle, in which each has 3 stages: plan, do, and see. Research data was obtained by observation and test. This research used a qualitative analysis consists of data reduction, data presentation and conclution. The result showed there was an increase learning outcomes of students in the subject of Capita Selecta Mathematics in middle school through the implementation of Lesson Study.